Home-based management of knee osteoarthritis during COVID-19 pandemic: literature review and evidence-based recommendations - Theofilos Karasavvidis; Michael T. Hirschmann; Nanne P. Kort; Ioannis Terzidis; Trifon Totlis (Journal of Experimental Orthopaedics, 2020)
Abstract Purpose To provide evidence-based recommendations for patients with severe knee osteoarthritis (OA), who had their knee surgery postponed due to the COVID-19 pandemic. Methods PubMed/Medline, Scopus and Cochrane Central databases were systematically reviewed for studies reporting outcomes of home-based treatments for knee OA. Due to between-study differences in treatment strategy and reporting methods the results were not pooled and findings of the current review were presented in a narrative manner. Results The comprehensive literature search yielded 33 eligible studies that were included in this review. Management is performed at home and consists of exercise, proper nutrition, physical therapy and use of corrective and assistive orthotics. Virtual education on self-management strategies should be part of coping with knee OA. Initiating an exercise programme involving gymnastics, stretching, home cycling and muscle strengthening is highly recommended. Obese patients are encouraged to set weight loss goals and adopt a healthy diet. Potential benefits but weak evidence has been shown for the use of knee braces, sleeves, foot orthotics or cushioned footwear. Walking aids may be prescribed, when considered necessary, along with the provision of instructions for their use. Conclusion When bridging the time to rescheduled surgery, it is essential to use appropriate home-based tools for the management of knee OA if pain is to be reduced and need for analgesics or opioid use is to be diminished while maintaining or even improving the functioning and avoiding further limitation of range of motion and subsequent muscular atrophies. Finally, none of these treatments may completely substitute for the life-changing effect of a total knee arthroplasty in patients with severe knee OA. Hence, the subsequent goal is to gradually and safely reinstate elective surgery.